Optimizing Spring Specification - Ramesh, Shreyas (My University, 2019)
Abstract The initial specification for the spring is very crucial for developing a concept design of the suspension system. The spring plays a major role in packaging and performance of the suspension system. The focus of this master thesis project is to obtain a detailed understanding of the different parameters and the sensitivity of the parameters during the selection of the spring for a suspension system. A detailed understanding is required when specifying the spring component and when selecting the spring dimensions for the suspension concept design. An analysis tool has been developed using Matlab which begins with calculating spring parameters to meet specific design requirements. The design process is done according to EN 13906-1 [8] standard and then checked if it meets the requirements of the suspension assembly. This data is then stored. The generated data is plotted in a graph based on the required parameters. These graphs are utilized to understand the relation between different parameters and how parameters related. Also, the reason for a not feasible solution is stored to understand more about the parameters. An optimization tool has been developed to identify the most suitable region for the design of the spring for a given requirement in the suspension concept. As cars are getting heavier, the packaging of the suspension system is more complex than before and posing new challenges to engineers. It is important to have the right ride and handling of the car by having a good suspension system for a car. Hence it is important to identify the crucial parameters and understand how they interact with each other.
Keywords: Optimization, Spring Specification, Suspension Spring